Supernova comunidade criativa: propostas para a geração de conexões e inteligência coletiva visando ao desenvolvimento de profissionais e marcas inseridos no universo de negócios criativos - Lima , Gabriel Corrêa (2020)
The general objective of this Master Course Conclusion Paper is to propose guidelines for building a community among creative business professionals, which promotes, among its participants, connections and a sense of belonging, feedback encouragement, and network development through collaborative content production, active participation, and creation of collective intelligence. The applicability of the research is in indicating directions for the construction of the “Supernova Creative Community”, which will allow for the development of a network with a high level of identification, a sense of belonging and quality content generation, as well as enabling the training of those involved, the feedback of knowledge and fostering collective intelligence and attracting new people to the network, favoring the qualified growth of professionals actively working and / or interested in the creative economy and, consequently, the development of this economic segment for Rio de Janeiro